Pemerintahan Digital dalam Penanganan Corona Virus Disease 2019 (COVID-19) di Kota Pekanbaru - Aulia Rizki, Raja; Andriyus, Andriyus (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
The global crisis of the COVID-19 pandemic has completely changed all aspects of people's lives. Digital is the new normal and the pandemic has emphasized the link between digitalization and development. Adaptive risk management can also be seen from the use of technology and information by the government through the relevant Ministries launched various applications that aims to make the handling of COVID-19 more effective, especially in health services and tracking and tracing as well as providing information. This paper is based on the research results using qualitative methods with exploratory analysis. There are three approaches in looking at digital governance strategy, namely the information systems strategy approach through a master plan for the field of information systems, alignment of information system functions and their application to achieve the organization's mission, and development of a shared vision of what the organization can achieve. Pekanbaru City Government in 2020 follows up on policies related to digital-based handling of COVID-19 governance by issuing several applications and handling information systems COVID 19 is like PPC 19, Waspada COVID 19, Data Rumah and Vaksin COVID 19.